Experimental Study on Optimized Adjustment of Ammonia Spraying in 300MW Unit. Issue 1 (February 2020) - Liu, Bo; Zhang, Peng; Li, Sha; Wei, Hongge; Zhu, Yue
Abstract: The experimental study on the optimization of ammonia injection in the denitration system of a 300MW coal-fired unit in a power plant. Under the premise of meeting the ultra-low emission standards of environmental protection requirements, the ammonia injection amount of the denitration device can be reasonably adjusted by adjusting the opening degree of the manual ammonia valve. It significantly improves the uniformity of the NOx concentration distribution in the denitration system. It eliminates local ammonia slip peaks and reduces ammonia slip rate. The deviation of the NOx concentration distribution at the outlet of the denitration system decreased by 70.1% and 46.7%, respectively. The ammonia slip concentration decreased by an average of 0.80 mg/m3 and 1.05 mg/m3. Ammonia consumption decreased by 8 kg/h and 15 kg/h, respectively.